Women in the Outdoors: A Gender Analysis in Sports Practices that Challenge Open Spaces (2024)
This article presents a reflection on various categories related to geographicalstudies such as gender inequality and the use of public space, specifically in relation to women’soutdoor sports practice, an activity linked to physical, mental and spiritual well-being of anyperson. Despite the relevance of sport in open spaces in the urban environment, accessibilityand safety continue to be violated issues that are crucial to guarantee its full enjoyment.Furthermore, for women, this participation is conditioned by the social construction of space.In this sense, concepts such as spaces of fear, areas with restricted hours, invisible borders andthe perception of needing male company act as barriers that limit their full right to use andenjoy public space.